2021
DOI: 10.1073/pnas.2104569118
|View full text |Cite
|
Sign up to set email alerts
|

Neural oscillatory activity serving sensorimotor control is predicted by superoxide-sensitive mitochondrial redox environments

Abstract: Significance Mitochondrial integrity and associated redox profiles have long been revered as key contributors to a host of age- and disease-related pathologies, which eventually lead to neuronal and behavioral dysfunction in the sensorimotor and other systems. However, the precise role of the mitochondrial redox environment in human sensorimotor brain systems and motor behavior remains poorly understood. Herein, we provide evidence for a strong predictive capacity of superoxide and its scavenger, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 77 publications
0
2
1
Order By: Relevance
“…Such data indicates heightened activity within the primary motor cortex, which is known to be the main output center for the cortical‐spinal tract. While we did not observe any motor performance differences between groups, numerous past studies have shown that the amplitude of the β‐ERD response is closely related to motor performance (Kurz et al, 2014, 2020; Spooner et al, 2021; Wiesman et al, 2020; Wilson, Fleischer, et al, 2011). Additionally, studies have shown that patients with Parkinson's disease, as well as cerebral palsy, exhibit weakened β‐ERD responses (Heinrichs‐Graham, Wilson, et al, 2014; Trevarrow et al, 2022).…”
Section: Discussioncontrasting
confidence: 72%
“…Such data indicates heightened activity within the primary motor cortex, which is known to be the main output center for the cortical‐spinal tract. While we did not observe any motor performance differences between groups, numerous past studies have shown that the amplitude of the β‐ERD response is closely related to motor performance (Kurz et al, 2014, 2020; Spooner et al, 2021; Wiesman et al, 2020; Wilson, Fleischer, et al, 2011). Additionally, studies have shown that patients with Parkinson's disease, as well as cerebral palsy, exhibit weakened β‐ERD responses (Heinrichs‐Graham, Wilson, et al, 2014; Trevarrow et al, 2022).…”
Section: Discussioncontrasting
confidence: 72%
“…Notably, studies from other groups have found that more pronounced MRBD predicted better task performance in individuals with ( Embury et al, 2019 , Trevarrow et al, 2022b ) or without pathological conditions ( Babiloni et al, 2000 , Heinrichs-Graham et al, 2020 , Van Hoornweder et al, 2022a , Van Hoornweder et al, 2022b ). However, some researchers observed no significant relationship between behavioural performance and MRBD ( Heinrichs-Graham et al, 2018 , Hübner et al, 2018 , Rossiter et al, 2014 , Schmiedt-Fehr et al, 2016 , Spooner et al, 2022 , Spooner et al, 2021 , Vallesi et al, 2010 ), while others claimed that higher MRBD was associated with worse performance ( Heinrichs-Graham and Wilson, 2016 , Johari and Behroozmand, 2020 , Kurz et al, 2020 , Xifra-Porxas et al, 2019 ). Aside from demographic variables (age range, gender distribution and health condition), experimental parameters, analysis approach, sample size, benzodiazepines using ( Hall et al, 2010 , Hall et al, 2011 , Jensen et al, 2005 ) and biological temporal rhythm ( Wilson et al, 2014 ), the inconsistency of results might be due to the influence of the level of spontaneous beta ( Hübner et al, 2018 , Lemm et al, 2009 , Rempe et al, 2022 ), cortical thickness (CT) ( Provencher et al, 2016 , Rempe et al, 2022 ) and measures of MRBD (absolute or relative value relative to resting state or baseline).…”
Section: Introductionmentioning
confidence: 99%
“…Movement is paramount to daily life and is needed for tasks such as securing food for nutrients and escaping dangerous environments. Motor coordination occurs at the level of the motor cortex ( Georgopoulos and Carpenter, 2015 ), where movement kinematics are converted into specific plans for carrying out voluntary movements ( Spooner et al, 2021 ). Populations of neurons exhibit beta frequency (e.g., 15–30 Hz) oscillatory activity, which supports the planning and execution of these voluntary movements.…”
Section: Introductionmentioning
confidence: 99%